COVID-19 Delta Variant: Perceptions, Worries, and Vaccine-Booster Acceptability among Healthcare Workers - Khalid Alhasan (MDPI AG, 2021)
Background: As the COVID-19 Delta variant has spread across the globe, healthcare workers’ (HCWs) knowledge, worries, and vaccine booster acceptance should be assessed. Methods: Online questionnaires aimed at HCWs in Saudi Arabia were distributed between 9 and 12 August 2021, aiming to evaluate HCWs’ perceptions and worries about the Delta variant as well as their feelings about receiving a booster-vaccine. Results: A total of 1279 HCWs participated, with 51.1% being physicians and 41.7% nurses. 92.5% were aware of the emergence of the Delta variant. Still, only 28.7% were found to have sufficient knowledge of the variant, and their level of worry about it was higher than their level of worry about the Alpha variant (2.32/5 versus 1.79/5). The main information sources cited by the participants were social media (50.5%), while 30.5% used scientific journals. Overall, 55.3% were willing to receive a vaccine booster, while one third would have preferred to receive a new mRNA vaccine specifically developed for the Delta variant. Factors associated with vaccine booster acceptance were receiving both vaccination doses (p = 0.008), believing that the Pfizer-BioNTech BNT162b2 vaccine is effective against variants (p < 0.001), and agreement that mixing/matching vaccines is effective against variants (p < 0.001). Conclusions: A high percentage of HCWs were aware of the Delta variant, but only a small fraction had decent quality of knowledge about it. The participants exhibited high worry levels and showed a modest acceptance of receiving a vaccine booster dose. These results should encourage public health officials to scale up educational efforts to disseminate reliable information about the different variants and provide recommendations about receiving a vaccine booster. Further research on methods to alleviate HCWs’ worries about emerging variants is warranted.